1986
DOI: 10.1103/physrevd.34.1237
|View full text |Cite
|
Sign up to set email alerts
|

Phase transition induced by cosmic strings

Abstract: The Rapid Communications section is intended for the accelerated publication of important new results. Since manuscripts submitted to this section are given priority treatment both in the editorial ofice and in production, authors should explain in their submittal letter why the work justifies this special handling. A Rapid Communication should be no longer than 3fi printed pages and must be accompanied by an abstract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 22 publications
1
38
0
Order By: Relevance
“…As long as this value remains small, the effective mass squared for the h in Eq. (30) remains positive. This makes jV 1 i a valid local minimum and admits a vortex sector jV ðstringÞ 1 i.…”
Section: Stability Analysis Of Jv ðStringþmentioning
confidence: 92%
See 1 more Smart Citation
“…As long as this value remains small, the effective mass squared for the h in Eq. (30) remains positive. This makes jV 1 i a valid local minimum and admits a vortex sector jV ðstringÞ 1 i.…”
Section: Stability Analysis Of Jv ðStringþmentioning
confidence: 92%
“…Specifically, when a cosmic string is present in a false vacuum, such a local minimum can be rendered unstable against decay to a vacuum of lower energy [28,29]. This process was studied by one of us [30] in the context of phase transitions in grand unified theory models. It was shown that generically, the presence of the cosmic string entailed the consequence that false vacuum would ''roll over'' smoothly to the true vacuum without recourse to quantum tunneling.…”
Section: Introductionmentioning
confidence: 99%
“…Decaying cosmic strings, which generalize the false vortex in 3 + 1 dimensions, were also studied in earlier work [32]. For the classical instability the effect was first investigated in the context of Grand Unified Theories in [33]. In those studies, cosmic strings are analogous to vortex lines in type II superconductors or in superfluid liquid helium.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The idea of the inhomogeneous decay of false vacua via solitons was initially pointed out by [19][20][21][22]. Then, in [23][24][25][26][27][28][29], applications to phenomenological model building were discussed in the context of field theories.…”
Section: Jhep06(2015)098mentioning
confidence: 99%